2020
DOI: 10.1016/j.ijnsa.2020.100007
|View full text |Cite|
|
Sign up to set email alerts
|

How organisational commitment influences nurses’ intention to stay in nursing throughout their career

Abstract: Background : The current COVID 19 pandemic brings into sharp focus the global necessity of having sufficient numbers of nurses and the dire impacts of nursing shortages throughout health systems in many countries. In 2020 retaining skilled experienced nurses continues to be a major global challenge. The dominant and consistent concentration of workforce research to date has focused on attitudinal factors including job satisfaction and burnout and there is limited research on how organisational com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 73 publications
4
26
0
2
Order By: Relevance
“…It is shown to fully mediate the relationships between job autonomy, intrinsic work motivation and turnover intention in the study by Galletta et al (2011) and partially mediate the link between job satisfaction and turnover intention in the study by Tarigan and Ariani (2015). In a recent study by Bell and Sheridan (2020), organisational commitment is found as the strongest predictor of nurses' intention to stay, surpassing the influence of job satisfaction and burnout.…”
Section: Perspective From the Social Exchange Theory: Organisational ...mentioning
confidence: 91%
“…It is shown to fully mediate the relationships between job autonomy, intrinsic work motivation and turnover intention in the study by Galletta et al (2011) and partially mediate the link between job satisfaction and turnover intention in the study by Tarigan and Ariani (2015). In a recent study by Bell and Sheridan (2020), organisational commitment is found as the strongest predictor of nurses' intention to stay, surpassing the influence of job satisfaction and burnout.…”
Section: Perspective From the Social Exchange Theory: Organisational ...mentioning
confidence: 91%
“…Previously conducted research showed that the willingness of the nurses to stay in the nursing profession is affected by many factors as the year of working experiences, job-related stress, marital status, organization factors, level of education, autonomy of the nurses in their works, and job satisfaction. 1 , 2 , 12 , 17 – 19…”
Section: Introductionmentioning
confidence: 99%
“…Vice versa, the more elements of the work that are not following the desires and value system adopted by the individual, the lower the level of satisfaction obtained. In addition, Bell & Sheridan (2020) states that job satisfaction can be a driving factor for increasing employee performance, which will improve organizational performance. According to Scaduto et al (2008), the work environment and work motivation positively and significantly affected job satisfaction.…”
Section: Introductionmentioning
confidence: 99%